Simulation of traffic congestion detection using VANETs - Anjum, N. (IEEE Computer Society, 2014)
In this progressive world traffic congestion is a critical issue. It results in huge amount of time and resources loss. Vehicles in congestion is a valuable parameter for drivers to anticipate the state of congestion. The proposed approach is based on relating the relationship of different transmission ranges with vehicle density. This research work uses a GrooveNet simulator, which is based on real street maps and plays a major role in discovering and disseminating congestion information. Our simulation results are based on average values of number of vehicles caught in congestion with respect to transmission range and vehicle density. Â© 2014 IEEE.